FRI0567-PC Using adaptive choice based conjoint (ACBC) analysis to study patients' preferences regarding pharmaceutical treatment for osteoarthritis (OA). (23rd January 2014) - Al-Omari, B.; Frisher, M.; Croft, P.; Sim, J.
Abstract : Background: Adaptive Choice Based Conjoint (ACBC) is a technique for eliciting and quantifying people's preferences. This is the first application of ACBC in rheumatology research. The advantage of this method is that it adapts to patients' responses to different medication scenarios. This research is concerned with the extent to which the benefits of medication are traded-off against serious adverse effects such as kidney impairment and stroke. Objectives: To determine the relative importance of 8 medication attributes, using the Adaptive Choice Based Conjoint. Methods: 11 participants were recruited from the Research User Group (RUG) at the Arthritis Research UK Primary Care Centre, Keele University, UK, to evaluate a newly developed ACBC questionnaire. Participants were over 50 years of age and suffering from OA in at least one of their joints. Participants completed an ACBC questionnaire involving 8 attributes: medication availability, frequency, route of administration, expected benefit, risk of addiction, risk of stomach side effects, risk of kidney and liver side effects, and risk of heart attacks and strokes. The relative importance of the 8 attributes, which sum to 100%, was calculated using Hierarchical Bayes (HB) estimation. Results: Rather than medication benefits being the top priority, the greatest impact on patients' preference regarding medication was the risk of kidney and liver side effects (22%), followed by the risk of heart attacks and strokes (17%), then the risk of stomach side effects (16%). The route of administration, frequency, and expected benefit were the least important factors influencing patients' preference (7%). Conclusions: ACBC reveals information about patients' preferences and the precise trade-offs that patients are willing to make. For example, OA patients are willing to trade off the benefits of medication for low risks of adverse effects. The benefits that patients expect from the medication are not very important when traded-off against serious medication adverse effects such as kidney and liver side effects. This shows the importance of making patients aware of OA medication side effects within the context of other treatment options. Acknowledgements: We are extremely grateful to Carol Rhodes and Adele Higginbottom (Patient and Public Involvement Co-ordinator and assistant at the Arthritis Research UK Primary Care Centre) for their effort to facilitate the RUG involvement. Special thanks to the Research User Group at the Arthritis Research UK Primary Care Centre, Keele University, UK, as this research work would not have been possible without their participation. Disclosure of Interest: None Declared